Evaluation of Social Protection Programs to Improve the Welfare of Indonesian Migrant Workers Deported from Malaysia at the Rumah Perlindungan Trauma Center (RPTC) Tanjungpinang, Riau Islands Province - Eddy Riyanto Oemar Husein; Bambang Satriawan; Nolla Puspita Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to evaluate social protection programs to improve the welfare of Indonesian Migrant Workers who are deported from Malaysia who are then provided with social protection services starting from pick-up, shelter at RPTC to repatriation to the area of origin. From the CIPP evaluation model used in this study, it was found: Context evaluation, social protection for migrant workers at RPTC is a crucial step in efforts to improve their welfare. Input evaluation, evaluation of the inputs that have been provided for the social protection of PMI at RPTC aims to measure the extent to which existing resources have been optimally utilized in improving the welfare of PMI which includes human resources, budget, facilities, policies, partnerships and information and data. In the Process Evaluation, researchers focus on activities or agendas that will or have been carried out by RPTC officers/employees. in this case the author found several processes of implementing the agenda, assisting personnel and the supervision process, namely by interviewing, validating the process and filling out questionnaires. Evaluation of results (product) is used to determine what decisions will be made next, the researcher concluded several interviews that said that this social protection service could improve the welfare of Indonesian Migrant Worker.